Parceria público-privada no Estado do Ceará: estudo de caso do Estádio Castelão em Fortaleza-Ce - Parente, Ticiana da Mota Gentil (2013)
Adequate infrastructure is essential for the growth of any country, especially in developingcountries such as Brazil, which in addition to significant fiscal constraints has large territorialextension. Countries that have faced this type of problem found as an alternative for its development the private partner, which over time took acting in different ways in this process. Many experiments have been adopted in the search for improvement and investment feasibility for the provision of public services. The present study is a quick account of this evolution and hold more specifically in the new mode of contracting through the Public-Private Partnership, in which the public seeks to improve the efficiency and effectiveness of their services through this modality. Discusses the processes involved for modeling studies, using or not the Expression of Interest Procedure as well as the framework and analysis of convenience and opportunity through Value for Money. Presents and analyzes the experience of the State of Ceará in the preparation, implementation and monitoring of the project implanted Arena Castelão, identifying their strengths and weaknesses